STUDIES ON THE BLACK SOOT DISEASE OF CORCHORUS OLITORIUS L. - OSIKANLU, Y. K. ODEBUNMI (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The black spot disease is reported on a popular Nigeria local vegetable, Corchorus olitorius L. The Curvularia State of Cochliobolus geniculatus Nelson was confirmed as the causal organism of the disease.   Four commonly grown cultivars of the vegetable were tested in the field for their reaction to the disease, Yaya and Angbadu were found to be more susceptible than Ex-Ogbomoso and Igbalode. All severely infected leaves were rendered unmarketable.